Impact of climate change on temperature variations and extrinsic incubation period of malaria parasites in Chennai, India: implications for its disease transmission potential - P. K. Kripa; P. S. Thanzeen; Nagaraj Jaganathasamy; Sangamithra Ravishankaran; Anupkumar R. Anvikar; Alex Eapen (Parasites & Vectors, 2024)
Abstract Background The global temperature has significantly risen in the past century. Studies have indicated that higher temperature intensifies malaria transmission in tropical and temperate countries. Temperature fluctuations will have a potential impact on parasite development in the vector Anopheles mosquito. Methods Year-long microclimate temperatures were recorded from a malaria-endemic area, Chennai, India, from September 2021 to August 2022. HOBO data loggers were placed in different vector resting sites including indoor and outdoor roof types. Downloaded temperatures were categorised by season, and the mean temperature was compared with data from the same study area recorded from November 2012 to October 2013. The extrinsic incubation period for Plasmodium falciparum and P. vivax was calculated from longitudinal temperatures recorded during both periods. Vector surveillance was also carried out in the area during the summer season. Results In general, temperature and daily temperature range (DTR) have increased significantly compared to the 2012–2013 data, especially the DTR of indoor asbestos structures, from 4.30 ℃ to 12.62 ℃ in 2021–2022, unlike the marginal increase observed in thatched and concrete structures. Likewise, the average DTR of outdoor asbestos structures increased from 5.02 ℃ (2012–2013) to 8.76 ℃ (2021–2022) although the increase was marginal in thatched structures and, surprisingly, showed no such changes in concrete structures. The key finding of the extrinsic incubation period (EIP) is that a decreasing trend was observed in 2021–2022 compared to 2012–2013, mainly in indoor asbestos structures from 7.01 to 6.35 days, which negatively correlated with the current observation of an increase in temperature. Vector surveillance undertaken in the summer season revealed the presence of Anopheles breeding in various habitats. Anopheles stephensi could be collected using CDC light traps along with other mosquito species. Conclusion The microclimate temperature has increased significantly over the years, and mosquitoes are gradually adapting to this rising temperature. Temperature negatively correlates with the extrinsic incubation period of the parasite. As the temperature increases, the development of the parasite in An. stephensi will be faster because of a decrease in EIP, thus requiring relatively fewer days, posing a risk for disease transmission and a hindrance to malaria elimination efforts. Graphical Abstract